Statistical Yearbook 2017 in infographics - Republic of Bulgaria. National Statistical Institute (Sofia: National Statistical Institute, 2018)
The publication is intended for a wider audience as statistical data are presented in a plain and easy understandable way. The current state and changes in the socio-economic and cultural life in the country are presented not in the traditional way in tables and text, but through infographics - images, graphics and other visualization tools.
Basic indicators about the demographic, social and economic development of the Republic of Bulgaria -- Territory, surface area and climate -- Environment -- Population and demographic processes -- Labour market -- House income, expenditure and consumption -- National accounts -- Price -- Investments -- Finance -- Exports and imports of goods -- Energy -- Non-financial enterprises -- Agriculture -- Forestry -- Industry -- Construction -- Transport -- Domestic trade; accommodation and food service activities -- Tourism -- Health -- Education -- Research and development activity -- Culture and art -- Criminality and justice
Keywords: Republic of Bulgaria; Bulgaria - Demography; Bulgaria - statistics; Bulgaria - socio-economic life; Bulgaria - cultural life